Economic Strategies and Prosperity in the Fatimid Dynasty: Contributions to Islamic Economic Thought - Meiska Fardani; Nuratika; Sirajuddin (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2024)
The Fatimid dynasty, known for its remarkable economic development, was one of the most prosperous periods in Islamic history. At its zenith, the dynasty enjoyed immense wealth, resulting in widespread prosperity among its citizens. The state’s revenues were primarily derived from two sources: community contributions and government enterprises. Community revenues included various forms of taxation such as al-iqtha', al-jizya, zakat, excise, al-ahbas, al-mawarits al-hasyriyyah, and al-amwal al-mashadirah. Government enterprises contributed through income from rentals of hotels and shops, as well as profits from trade, industry, and other state-owned economic sectors. The Fatimids invested significantly in diverse economic areas such as agriculture—cultivating wheat, sugarcane, and fruits with an advanced irrigation system; crafts—manufacturing ships, weapons, textiles, and household items; and both domestic and international trade. These economic advancements played a crucial role in maintaining the dynasty’s power for over 250 years (297-567 H / 909-1171 AD). This study provides a comprehensive examination of the Fatimids’ economic policies and strategies, highlighting their contributions to Islamic economic thought and their impact on subsequent developments in the region.